2023
DOI: 10.1242/bio.059650
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for STAT3 and its target, TFCP2L1, in self-renewal of naïve pluripotent stem cells in vivo and in vitro

Abstract: We previously demonstrated gradual loss of epiblast during diapause in embryos lacking components of the LIF/IL6 receptor. Here, we explore requirement for the downstream signalling transducer and activator of transcription, STAT3 and its target, TFCP2L1, in maintenance of naïve pluripotency. Unlike conventional markers, such as NANOG, which remains high in epiblast until implantation, both STAT3 and TFCP2L1 proteins decline during blastocyst expansion, but intensify in the embryonic region after induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The Hoechst 33342 channel was used for nuclei segmentation in three dimensions using ZeroCostDL4Mic StarDist via Google colaboratory ( Schmidt et al, 2018 ; Weigert et al, 2018 ). For details on software training for embryo images, see Kraunsoe et al (2023) .…”
Section: Methodsmentioning
confidence: 99%
“…The Hoechst 33342 channel was used for nuclei segmentation in three dimensions using ZeroCostDL4Mic StarDist via Google colaboratory ( Schmidt et al, 2018 ; Weigert et al, 2018 ). For details on software training for embryo images, see Kraunsoe et al (2023) .…”
Section: Methodsmentioning
confidence: 99%
“…MTHFD1 is an enzyme involved in folate metabolism [ 115 , 116 , 117 ], and although it was reported as a potential stem cell marker by Maguire et al and Bhattacharya et al [ 51 , 118 ], there is no other knowledge in regard to its role in stem cell pluripotency, while its polymorphisms have been associated with therapeutic response to methotrexate in childhood acute lymphoblastic leukemia [ 119 , 120 , 121 ]. STAT3 is well known as a transcription factor for its role in the regulation of the self-renewal of embryonic stem cells [ 122 , 123 , 124 ], suggesting that its expression in SBSCs may indeed promote their self-renewal.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that Tfcp2l1 is a downstream target of the canonical Wnt/β-catenin, STAT3 and FGF/MEK signalling pathways and plays a pivotal role in promoting embryonic stem cell self-renewal [ 34 , 35 ]. In addition, the lower Kcns3 levels provide a new molecular mechanism of neuron dysfunction in schizophrenia, which encodes potassium channel-associated subunits [ 36 ].…”
Section: Discussionmentioning
confidence: 99%